Variation in the Verbal Morphology of Galician in the Region of O Ribeiro - Louredo Rodríguez, Eduardo (Madrygal. Revista de Estudios Gallegos, 2024)
This study analyses a series of linguistic variables that have in common their belonging to the field of verbal morphology. The data for this study was obtained through questionnaire-based interviews with thirty people from ten different places. This data was complemented with the transcription of semi-structured interviews with the same individuals. The purpose of this research is to establish how the variants studied are subject to processes of linguistic change, observable in the linguistic usage of three groups of people of different ages. The appearance of different variants is due both to internal factors (analogy or simplification of the system) and external factors (contact with other linguistic varieties); the expansion of some of them is attributable to contact with Castilian or with other similar Galician varieties.